Investment prioritizing in high tech industries based on SWARA-COPRAS approach - Zolfani, Sarfaraz Hashemkhani; Bahrami, Mohsen (Technological and Economic Development of Economy, 2014)
One of the symbols of developed countries is high tech industries. High tech industries have a large margin. One of the priorities of developing countries is the progress in this type of industries. The decisions about priority of developing an industry are so hard that seems it should be seen from different perspectives. This research is focused on decision and policy making in priority of high tech industries in Iran. Two MCDM methods are applied in this research for decision making in this area. SWARA for evaluating and weighting criteria and COPRAS for evaluating and ranking alternatives are applied. Eleven experts from different fields participated in this research to make decision with SWARA and COPRAS. Four high tech industries including Biomedical Micro Electromechanical Systems (BioMEMS), Nano Technology, Biotechnology, and Biomedical Engineering were selected for this research. These industries were selected based on the potential of Iran. Final result shows that Nanotechnology is at the top of priorities in Iran. Authors believe that this methodology can be useful in other issues in this and other areas of research.